Resurgence of Clinical Malaria in Ethiopia and Its Link to Anopheles stephensi Invasion - Guofa Zhou; Hiwot S. Taffese; Daibin Zhong; Xiaoming Wang; Ming-Chieh Lee; Teshome Degefa; Dejene Getachew; Werissaw Haileselassie; Dawit Hawaria; Delenasaw Yewhalaw; Guiyun Yan (Pathogens, 2024)
The invasion of Anopheles stephensi into Africa poses a potential threat to malaria control and elimination on the continent. However, it is not clear if the recent malaria resurgence in Ethiopia has linked to the expansion of An. stephensi. We obtained the clinical malaria case reports and malaria intervention data from the Ethiopian Ministry of Health (MoH) for the period 2001–2022. We analyzed clinical malaria hotspots and investigated the potential role of An. stephensi in the 2022 malaria outbreaks. Clinical malaria cases in Ethiopia decreased by 80%, from 5.2 million cases in 2004 to 1.0 million cases in 2018; however, cases increased steadily to 2.6 million confirmed cases in 2022. Plasmodium vivax cases and proportion have increased significantly in the past 5 years. Clinical malaria hotspots are concentrated along the western Ethiopian border areas and have grown significantly from 2017 to 2022. Major malaria outbreaks in 2022/2023 were detected in multiple sites across Ethiopia, and An. stephensi was the predominant vector in some of these sites, however, it was absence from many of the outbreak sites. The causes of recent upsurge in malaria in Ethiopia may be multi-factorial and it is a subject of further investigation.